2018
DOI: 10.3389/fnins.2018.00613
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal in vivo Diffusion Tensor Imaging Detects Differential Microstructural Alterations in the Hippocampus of Chronic Social Defeat Stress-Susceptible and Resilient Mice

Abstract: Background: Microstructural alterations in the hippocampus may underlie stress-related disorders and stress susceptibility. However, whether these alterations are pre-existing stress vulnerability biomarkers or accumulative results of chronic stress remain unclear. Moreover, examining the whole hippocampus as one unit and ignoring the possibility of a lateralized effect of stress may mask some stress effects and contribute to the heterogeneity of previous findings.Methods: After C57BL/6 mice were exposed to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Ex-vivo diffusion MRI and diffusion kurtosis imaging studies documented specific microstructural changes in the hippocampus, amygdala, and several cortical areas of rats exposed to chronic stress (Khan et al, 2016a(Khan et al, ,b, 2018. These findings have been confirmed by a recent in vivo imaging experiment (Liu X. et al, 2018).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Ex-vivo diffusion MRI and diffusion kurtosis imaging studies documented specific microstructural changes in the hippocampus, amygdala, and several cortical areas of rats exposed to chronic stress (Khan et al, 2016a(Khan et al, ,b, 2018. These findings have been confirmed by a recent in vivo imaging experiment (Liu X. et al, 2018).…”
Section: Introductionsupporting
confidence: 60%
“…They also observed increased FA in the hypothalamus and hippocampal CA3 and different structural covariance between brain regions in susceptible and resilient mice (Anacker et al, 2016). Others reported on a significantly lower FA in the right ventral hippocampus of the stress-susceptible mice prior to the chronic stress exposure, suggesting that pre-existing microstructural abnormalities may result in stress susceptibility (Liu X. et al, 2018). Another study documented substantial increase (45%) in the volume of the amygdala of a rat strain that is susceptible to the repeated stress procedure (F344 rats; Bourgin et al, 2015).…”
Section: Correlation Between the Dti Parameters And Cognitive Behaviormentioning
confidence: 92%
“…Mean Ď® SEM. has been associated with alterations in microRNA expression (Muñoz-Llanos et al, 2018) and microstructural alterations in the dorsal hippocampus (Liu et al, 2018). We have recently shown that the dorsal hippocampus expresses fewer NMDA receptors in the extrasynaptic location (Tse et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Integrated with fMRI, these technologies can map the downstream effects of local manipulations on global brain activity [212][213][214] . The neurobiology of stress can also be studied through diffusion tensor imaging 215 , magnetoencephalography 216 , calcium-based fiber photometry 217,218 , and molecular fMRI 214 . Combined with fMRI, these multimodal methods allow researchers to collect complementary and multi-dimensional information across spatiotemporal scales on the same animal.…”
Section: Technological Advancesmentioning
confidence: 99%